Friday Night Comics in Dark Times - Mattox, Jake (Radical Teacher, 2025)
This essay explores, in the context of the “dark times” facing public education at all levels in the United States, alternative approaches to and locations of teaching and learning, such as the weekly “Friday Night Comics” series hosted on Zoom. Drawing upon conversations with organizers and participants, plus research in comics, DIY, and critical university studies, I argue for the increasing importance of non-institutional spaces and forms of learning.